Make it Japanese simple recipes for everyone - McClenny, Rie; Lemoine, Sanae; Afuso, Jeni (New York Clarkson Potter/Publishers, 2023)
"Learn the building blocks of authentic Japanese home cooking with 85 satisfying, soulful, everyday recipes from the beloved BuzzFeed Tasty food personality. Make It Japanese reflects Rie's journey living in the United States for over 15 years and learning to cook heartfelt recipes from home from scratch, often using only ingredients from her local supermarket. She draws inspiration from the nourishing food her mom cooked throughout her childhood and her extensive knowledge of Japanese cuisine and ingredients that she brought to life in an American kitchen. In her debut cookbook, Rie shares just how approachable Japanese home cooking can be, no matter where you are. She presents a collection of comforting, homestyle recipes that use just a handful of easy-to-find Japanese ingredients and simple, essential cooking techniques, like making rice bowls (donburi) and gently simmering vegetables and proteins to delicious effect. Each accompanied by bright, beautiful photography, recipes include traditional dishes with a twist, like Loaded Veggie Miso Soup with kale and sweet potatoes, Roasted Cauliflower Go-mae topped with a toasted sesame dressing, and umami-packed Miso Carbonara Pasta, alongside can't-miss classics like sticky Teriyaki Meatballs, ginger-spiked Japanese-Style Fried Chicken, and Katsudon, rice bowls topped with crispy pork cutlets and egg. Whether making dinner on a busy weeknight or hosting a multi-course banquet, Make It Japanese is the ideal resource and perfect introduction to the world of Japanese cuisine, ingredients, and cooking techniques"--
Introduction -- How to stock a Japanese pantry -- Essential Japanese kitchen tools -- Vegetables -- Meat -- Seafood -- Rice -- Noodles -- Gatherings -- Sweets & breads.
Includes index.
113260
Keywords: Cooking, Japanese; Cuisine japonaise; Cooking / Regional & Ethnic / Japanese; Cookbooks